Ecological sensitivity and global legal pluralism : rethinking the trade and environment conflict - Perez, Oren (International studies in the theory of private law., 2004)
The tension between trade liberalisation and environmental protection has received remarkable attention since the establishment of the WTO. It has been the subject of a wide-ranging debate, and is one of the central themes of the anti-globalisation movement. This book explores that debate. It argues that by focusing on the WTO, the debate has failed to recognise the institutional and discursive complexity in which the trade-environment conflict is embedded. A legal investigation of this nexus requires a framework of inquiry, in which this complexity can be elucidated - a model of global legal.